Non-English Major Students' Strategies in Improving English Speaking Skills as an Effort to Optimize Islamic Da'wah in the Global Era - Alimuddin, NurAulia Amalia (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study aims to analyze the learning strategies used by non-English major students to improve their English-speaking skills, as well as to identify the factors influencing their choice of strategies and the challenges they encounter during the learning process. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation involving several non-English major students who actively practiced speaking English. The findings revealed that students applied various learning strategies, including cognitive, metacognitive, social, and affective strategies. Factors influencing strategy selection included motivation, prior learning experiences, social support, and access to technology. Meanwhile, the main challenges faced by students were limited vocabulary, fear of making mistakes, and lack of opportunities to practice speaking. Overall, the study highlights that non-English major students are capable of improving their speaking skills through independent, creative, and context-based learning strategies, despite the constraints of formal learning environments.